EFFECTIVINESS OF USING E-FILLING AND TAXPAYER’S COMPLIANCE LEVEL IN REPORTING SPT AT THE SELONG TAX SERVICES, EXTENTION AND CONSULTATION OFFICE (KP2KP SELONG), DURING 2011-2020 - Alwi, Muhammad (Jurnal Aplikasi Perpajakan, 2024)
The aim of the study was to analize of the effectiveness of using e-filling and the level of tax payer’s compliance in reporting SPT before and after using e-filling at The Selong Tax Services, Extention and Consultattion office (KP2KP Selong) during 2011-2020. The data is secondary data such as the number of registered tax payers, the number of tax payer reporting and not reporting SPT during 2011-2020. Based on data anlayses it is known that both before and after using e-filling in reporting SPT has not cange significantly, and is still classified as very law. The average SPT reporting during 2011-2017, before using e-filling, was 37% (very law catagory), and after using e-filling, 2018-2020, is 38,20% (still very law catagory). So using e-filiing is not efektive yet. The Compliance of tax payer, in term of percentage of reporting SPT, even thoug there was increase in SPT reporting of 1.20%, after using e-filling, is very law catagory. The law level compliance of the taxpayer in reporting of SPT due to lack of awareness and lack understanding of modern tax system.There needs to be continuity of conselling or dissamination of the modern tax system and use of e-filling to taxpayer.